The Paracoccidioides Cell Wall: Past and Present Layers Toward Understanding Interaction with the Host - Puccia, Rosana; Vallejo, Milene C.; Matsuo, Alisson L.; Longo, Larissa V. (Frontiers in Microbiology, 2011)
The cell wall of pathogenic fungi plays import roles in interaction with the host, so that its composition and structure may determine the course of infection. Here we present an overview of the current and past knowledge on the cell wall constituents of Paracoccidioides brasiliensis and P. lutzii. These are temperature-dependent dimorphic fungi that cause paracoccidioidomycosis, a systemic granulomatous and debilitating disease. Focus is given on cell wall carbohydrate and protein contents, their immune-stimulatory features, adhesion properties, drug target characteristics, and morphological phase specificity. We offer a journey towards the future understanding of the dynamic life that takes place in the cell wall and of the changes that it may suffer when living in the human host.